Does collaborative use of the Internet affect Reading Comprehension in Children? - Sugata Mitra (Commonwealth of Learning, 2019)
This paper examines the effect of the Internet on the reading comprehension of children reading together in groups. First, we describe an experiment to determine if children reading together off the Internet from big screens, can read at a higher comprehension level than children reading the same text alone. The results from this small-sample study are then compared to the results from a larger study across many locations in India. We find that children with low reading comprehension levels to start with can read and understand text at a level higher than expected from them, if they are reading together and have the Internet available. Moreover, in the process of doing this kind of ‘self-organised’ reading, their individual reading comprehension increases. This way of reading may provide a simple and reliable method to improve the reading comprehension of children in their own, or foreign, languages.